Long-acting growth hormone for pediatric GHD: insights into molecular modification and clinical application - Gu, Jianyang; Qiao, Yongbo; Gong, Ping (Frontiers in Endocrinology, 2026)
Long-acting growth hormone (LAGH) therapies represent a paradigm shift in the management of growth hormone deficiency (GHD), alleviating the burden of daily injections. This review comprehensively evaluates the LAGH landscape, detailing molecular engineering strategies that extend half-life, and assessing the pharmacokinetics, efficacy, and safety of globally approved agents and candidates in China. By integrating pivotal trial data with recent international consensus, we provide a practical framework for clinical management, including patient selection and monitoring. Furthermore, we identify critical knowledge gaps in the field, highlight the need for high-quality real-world evidence, and explore promising future directions. This review thereby provides a holistic perspective on the current progress and unmet needs in LAGH therapy.